(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
Vesicoureteral reflux (VUR) is a significant urological condition in children, characterized by the retrograde flow of urine from the bladder into the ureters and kidneys. This condition can lead to severe complications such as recurrent urinary tract infections (UTIs) and potential kidney damage. This study investigates the effectiveness and safety of anti-reflux surgical interventions in children diagnosed with VUR, specifically comparing ureteral reimplantation and endoscopic treatments. The study includes a retrospective analysis of 100 pediatric patients with grade III-IV VUR who underwent surgical treatment between 2018 and 2023. The findings indicate that while ureteral reimplantation offers a higher success rate in resolving VUR, endoscopic treatments are less invasive and associated with fewer complications, albeit with a slightly higher recurrence rate of reflux. The study concludes that the choice of surgical treatment should be individualized based on the patient’s specific condition and overall health.